Another Radical Expression Question

Algebra Level 1

Look at the question above and answer.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Isabella Yan
Feb 6, 2015

This is my solution

Noel Lo
Jul 21, 2016

If 2 < x < 3 2<x<3 , then ( x 2 ) 2 = x 2 \sqrt(x-2)^2=x-2 while x 3 = ( x 3 ) = 3 x |x-3|=-(x-3)=3-x such that we have x 2 + 3 x = 1 x-2+3-x=\boxed{1} where the x's actually cancel out each other.

James Kumar
Feb 7, 2015

since,2<x<3,i.e,x=[2.1,2.9]. so, sqrt( (x-2)^2 ) = |x-2| = [0.1 , 0.9]

&&

|x-3| = [0.1 , 0.9] or, simply [0.9 , 0.1]

Hence,sum i.e., ? = 1.

Note: sqrt( X^2 ) = |X|.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...